Az integráció hatása az EU tagországok külkereskedelmére - vizsgálatok gravitációs modellel (Impacts of the Integration on Trade of EE Members - A Gravity Model Approach) - Ildiko Virag-Neumann (DETUROPE)
The gravity model has been extensively used in international trade research for the last 40 years because of its considerable empirical robustness and explanatory power. Since their introduction in the 1960’s, gravity models have been used for assessing trade policy implications and, particularly recently, for analyzing the effects of Free Trade Agreements on international trade. The objective of this dissertation is to review the recent empirical literature on gravity models, highlight best practices and provide an overview of EU integration effects on international trade as reported by relevant gravity model-based studies over the past decade. Examining the trade prospects for the new European Union (EU) member states is an important issue in the context of European eastward enlargement and greater economic integration with its immediate neighbours. I use a gravity equation for a panel data set of bilateral export flows from EU12, EU15 over the 2000-2010 period. The potential trade volumes are calculated from a gravity model.